Motion of a Ball from Crease to Boundary in a Game of Cricket - Maitra, Soumendra Nath (SCHOOL SCIENCE, 2018)
This is a model to calculate the motion of a ball hit by a batsman to score a boundary. The ball hits the ground, bounces several times and then grazes the ground to reach the boundary line evading intercept by any fieldsman. With given initial velocity, time taken by the ball to cross the boundary line covering the distance between the batsman and the ball touching the boundary line is determined. Herein the minimum initial velocity of the batted ball and its corresponding direction to strike a ‘four’ are also determined. Some numerical examples are also cited.